Analysis of the Impact of e-Health Technology on Health: A Systematic Review - Alvaro Torres-Cavero; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
In recent times the use of e-health technology has become a necessity for the application in different clinical cases being used depending on the type of disease and type of care required by the patient, therefore. This article is a systematic review of the literature on the analysis of the implementation of e-health technology for patient care, which allows the collection of information necessary for subsequent follow-up and/or treatment of infectious diseases, one of the main ones being the current COVID-19 virus.  The present review was carried out in different bibliographic sources from which 81 scientific articles related to the research topic were collected, which will be included or excluded according to our own criteria, being obtained from the databases of Proquest, Scopus, ScienceDirect, Scielo. Where it is subsequently concluded that the implementation of an application based on e-health technology allows us to provide this attention to the patient, which is beneficial since we currently have many easily accessible devices for the users.
Keywords: e-health; treatment; infectious diseases; COVID-19; systematic review.